A New Modified MPPM for High‐Speed Wireless Optical Communication Systems. Issue 2 (1st April 2013) - Rouissat, Mehdi; Borsali, Riad A.; Chikh‐Bled, Mohammad E.
Abstract : Previous work proposed combining multipulse pulse position modulation (MPPM) with pulse amplitude modulation to form multipulse amplitude and position modulation (MPAPM), which is a hybrid modulation that results in an improvement in bandwidth efficiency but a degradation in power efficiency. In this paper, to achieve greater power efficiency and a better data rate, we propose multipulse dual amplitude‐width modulation, based on MPAPM and pulse width modulation. The proposed scheme shows a remarkable improvement in data rate and a 1.5‐dB improvement in power efficiency over MPAPM, while sustaining the bandwidth efficiency. After introducing symbol structure, we present the theoretical expressions of spectral efficiency, the power requirements, and the normalized data rate, as well as the results of comparing the proposed modulation to MPPM and MPAPM.